Structural Break Analysis and Price Transmission of Bulk Cooking Oil in the Indonesian Palm Oil Agribusiness System - Jihan Zhafira; ⁠Dedi Budiman Haki; Faroby Falatehan (Postgraduate, University of Mataram, 2026)
Volatility in Indonesia’s bulk cooking oil market has increased since the COVID-19 pandemic, disrupting household consumption and threatening national food security. This study analyzes structural breaks in the price dynamics of Fresh Fruit Bunches (FFB), Crude Palm Oil (CPO), and bulk cooking oil, as well as asymmetric price transmission before and after key government interventions. Weekly data from 2020–2024 were examined using the Additive Outlier test, the NARDL model, the Hatemi-J asymmetric causality test, and the Wald test. The results reveal a significant structural break in April 2022, associated with the CPO export ban, DMO/DPO policies, and the implementation of a retail price ceiling (HET). Before the break, short-run price transmission was asymmetric but became symmetric in the long run. After the intervention, short-run transmission was symmetric, while long-run asymmetry persisted, indicating downward price rigidity and reduced market efficiency. These findings suggest that government intervention effectively stabilized short-term prices but created long-term structural distortions. Strengthening distribution efficiency, improving price transparency, and adopting more adaptive policies are essential to enhance market efficiency and economic food resilience.